Copolymeric micelles as efficient inert nanocarrier for hypericin in the photodynamic inactivation of Candida species. (29th April 2019) - Sakita, Karina M; Conrado, Pollyanna CV; Faria, Daniella R; Arita, Glaucia S; Capoci, Isis RG; Rodrigues-Vendramini, Franciele AV; Pieralisi, Neli; Cesar, Gabriel B; Gonçalves, Renato S; Caetano, Wilker; Hioka, Noboru; Kioshima, Erika S; et al.
Aim: To evaluate the efficacy of photodynamic inactivation (PDI) mediated by hypericin encapsulated in P-123 copolymeric micelles (P123-Hyp) alone and in combination with fluconazole (FLU) against planktonic cells and biofilm formation of Candida speciesMaterials & methods: PDI was performed using P123-Hyp and an LED device with irradiance of 3.0 mW/cm 2 .Results: Most of isolates (70%) were completely inhibited with concentrations up to 2.0 μmol/l of HYP and light fluence of 16.2 J/cm 2 . FLU-resistant strains had synergic effect with P123-HYP-PDI and FLU. The biofilm formation was inhibited in all species, in additional the changes in Candida morphology observed by scanning electron microscopy.Conclusion: P123-Hyp-PDI is a promising option to treat fungal infections and medical devices to prevent biofilm formation and fungal spread.